Author Correction: Genomic analysis of sewage from 101 countries reveals global landscape of antimicrobial resistance (Nature Communications, (2022), 13, 1, (7251), 10.1038/s41467-022-34312-7) - Munk P. (2023)
In this article, the author name Antoinette Ngandjio was incorrectly written as Antoinette Ngandijo. In this article, the affiliation details for Author Sara Cuadros-Orellana were incorrectly given as ‘Centro de Biotecnologνa de los Recursos Naturales, Facultad de Ciencias Agrarias y Forestales, Talca, Chile’ but should have been ‘Universidad Catolica del Maule, Centro de Biotecnología de los Recursos Naturales, Facultad de Ciencias Agrarias y Forestales, Talca, Chile’. The original article has been corrected.